2014
DOI: 10.4102/hsag.v19i1.684
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic use of music as experienced by cardiac surgery patients of an intensive care unit

Abstract: Patients perceive the intensive care unit (ICU) as being a stressful and anxiety-provoking environment. The physiological effects of stress and anxiety are found to be harmful and therefore should be avoided in cardiac surgery patients. The aim of the study on which this article is based was to describe cardiac surgery patients’ experiences of music as a therapeutic intervention in the ICU of a public hospital. The objectives of this article were to introduce and then expose the cardiac patients to music as pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The present study supports the various literatures that have investigated the anxiolytic effects of music, generally conducted within medical environment. Bhana et al (2014) reported that therapeutic use of music is highly beneficial to ICU patients who have had cardiac surgery, and that together with routine postoperative care, it can promote holistic patient care. Nilsson (2008) conducted a systemic review to check the anxiety and pain reducing effects of musical intervention in surgical, preoperative and post-operative patients, and concluded that music therapy reduces pain and anxiety in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study supports the various literatures that have investigated the anxiolytic effects of music, generally conducted within medical environment. Bhana et al (2014) reported that therapeutic use of music is highly beneficial to ICU patients who have had cardiac surgery, and that together with routine postoperative care, it can promote holistic patient care. Nilsson (2008) conducted a systemic review to check the anxiety and pain reducing effects of musical intervention in surgical, preoperative and post-operative patients, and concluded that music therapy reduces pain and anxiety in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Music positively influences health and well-being, reducing the feeling of stress (MacDonald, 2013 andLaukka, 2007). Music therapy used as a relaxation aids (Krout, 2001;Curtis, 1986) within the medical environment and Music helps fasten post exercise recovery (Savitha et al, 2010), while the effectiveness of music in cardiac care unit in order to reduce stress and anxiety in cardiac patients has been established (Bhana et al, 2014 andBradt et al, 2009). Music therapy has also shown effect on the anxiety in palliative care unit (Calovini, 1993;Gallagher, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…32 Byly popsány i situace, kdy pacienti, kteří zažili mnoho stresu a bolesti, se rozhodli poslouchat hudbu kratší dobu v určitých časových úsecích nebo ji raději neposlouchali. 33 Novější studie pochází z Číny, 34 Spojených států, 35 Turecka 36 a Iránu 37 a orientují se spíše na vliv poslechu hudby na redukci pooperačního strachu, úzkosti a bolesti.…”
Section: Diskuseunclassified
“…počet sezení 1× denně před operací nebo 2× denně první, druhý, třetí den po operaci a výběr doby, kdy je možné hudbu aplikovat (u typů zákroků se liší možnosti), hlasitost 50 až 60 decibelů, výběr hudby dle pacienta či relaxační. Někteří výzkumníci považovali hudbu z vlastní kultury pacienta za efektivnější, 33,37,38 proto výzkumy spojené s poslechem tradiční hudby dané země nemohou být zobecňovány na populaci. 39 V naší studii pacienti vybírali z deseti hudebních žánrů a nejčastěji volili country nebo popovou hudbu.…”
Section: Diskuseunclassified